The Model of Sports Talent Management in the Field of Track and Fields in the Schools of Iraq - Mohammad Ghazi ahmed; Farzam Farzan; Morteza Dousti (دراسات وبحوث التربية الرياضية)
The general purpose of this research is to develop a model for managing sports talents in the field of track and field in Iraqi schools. The current research method was qualitative. Which was used to build the conceptual model of the research based on the theory of Glasser Ground. The research community consists of professors and faculty members in the faculties of physical education and sports sciences, the president and vice presidents of the Athletics Federation, former track and field players and coaches working in Iraq and some athletes in the national team, after interviewing 20 people, the researcher noticed that the results were repetitive, so to ensure the similarity of the results, 3 new interviews were conducted and according to the results, thus the theoretical saturation was determined through 22 interviews. Based on the results of the qualitative data analysis obtained from the interview, the presentation of the final model of the research consists of: organizing the training system, coordinating track and field leaders, developing talents and physiological dimensions. Indicators before identifying talents The recruitment process and training of professional coaches with talent identification and improving the quality and quantity of sports and sports spaces, talent maintenance, and supporting research projects in terms of effective indicators after identifying talents